KEMAMPUAN MEMBACA CEPAT PESERTA DIDIK KELAS X SMA NEGERI 4 PONTIANAK - Chania, Auly; Wartiningsih, Agus; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to analyze the speed of reading ability of grade X students of SMA Negeri 4 Pontianak. The method used is descriptive to describe the ability of students in speed reading, with the form of research that is qualitative. The subjects of this study were 34 students of class X G SMA Negeri 4 Pontianak. The data obtained is the result of the reading speed of students in the discourse that has been given in the form of speed of reading ability test results, determining the main idea of paragraphs, and understanding the content of the discourse. The results of the analysis of the speed of reading ability of grade X students of SMA Negeri 4 Pontianak based on the ideal speed category for high school students are 14 students who have speeds below average, people with average / ideal speed, and 15 people above average. Furthermore, the results of determining the main idea of the students' paragraph were three people got good grades (B), nine people got enough marks (C), and 16 people got less marks (D). Finally, the results of the analysis of the ability to understand the content of discourse of grade X students of SMA Negeri 4 Pontianak were four people who got a very good grade category (A), 10 people got a good grade category (B), four people 129 got a sufficient score category (C), and 16 people got a less score category (D).